2021
DOI: 10.1371/journal.pone.0240278
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of muscle mass in adult male mice is independent of testosterone

Abstract: Testosterone is considered a potent anabolic agent in skeletal muscle with a well-established role in adolescent growth and development in males. However, the role of testosterone in the regulation of skeletal muscle mass and function throughout the lifespan has yet to be fully established. While some studies suggest that testosterone is important for the maintenance of skeletal muscle mass, an understanding of the role this hormone plays in young, adult, and old males with normal and low serum testosterone le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
5
10
0
Order By: Relevance
“…Interestingly, low testosterone levels (<10 nmol/L) maintained leg muscle mass and strength. This latter finding is in keeping with research in rodents that shows testosterone is not needed for muscle maintenance in adult male mice [ 35 ]. In this study, orchidectomised mice aged from young through to old were assessed for muscle mass after 28 days of testosterone depletion.…”
Section: Male Physiology Provides An Athletic Performance Advantagesupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, low testosterone levels (<10 nmol/L) maintained leg muscle mass and strength. This latter finding is in keeping with research in rodents that shows testosterone is not needed for muscle maintenance in adult male mice [ 35 ]. In this study, orchidectomised mice aged from young through to old were assessed for muscle mass after 28 days of testosterone depletion.…”
Section: Male Physiology Provides An Athletic Performance Advantagesupporting
confidence: 90%
“…Only the youngest mice showed reduced muscle mass, while the older, adult mice showed no effect on muscle mass. Therefore, it appears that testosterone may not be critical for maintenance of muscle mass in mature male mice [ 35 ]. In females, testosterone administration to raise circulating levels from 0.9 nmol/L to 4.3 nmol/L in young women (average 28 years) increased muscle mass and strength, as well as enhanced athletic performance as evidenced by time to exhaustion and Wingate testing [ 36 ].…”
Section: Male Physiology Provides An Athletic Performance Advantagementioning
confidence: 99%
“…In contrast to the preferential effect of estrogen on females, testosterone plays a key role in body composition, as well as in glucose and lipid metabolism, exerting an inhibitory effect on insulin sensitivity in males [ 49 , 50 , 51 ]. In line with these results, the differences in TWG observed between young males and females may also be associated with the effect of sex hormones, since testosterone favors muscle mass accretion [ 52 ], and differences disappear with age where testosterone concentrations are lower. A limitation of the present study is that adipocytes from rodent WAT were not isolated and cultured in order to study the hormone production related to energy homeostasis, and further investigations analyzing both the hormones and the mechanisms related to the improvement of the adipose tissue function in female mice are warranted.…”
Section: Discussionmentioning
confidence: 79%
“…Previously, Ribeiro et al (2018) associated higher testosterone levels observed at 90 days with saponins found in Colocasia esculenta . Although the pathways, based on which saponin increases rat serum testosterone, require further studies (Liu et al , 2017), testosterone – as the main androgen and anabolic steroid – promotes protein synthesis and skeletal muscle growth throughout individuals’ lives (Davidyan et al , 2021; Shin et al , 2018; Liu et al , 2017). Saponins associated with protein and amino acids found in C. esculenta had anabolic effects on the body lean mass of young healthy male rats, who were not subjected to physical training in the current study.…”
Section: Discussionmentioning
confidence: 99%